Analisis Evaporative Air Cooler Dengan Temperatur Media Pendingin Yang Berbeda - Listiono, Hendra; Aziz, Azridjal; Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Evaporative cooling process occurs when water vapor is added to air having a relative humidity of below 100%. Relative humidity is a value that is contained in the temperature of the dry bulb and wet bulb temperature of the air. the lower the relative humidity, the greater the potential for evaporative cooling. The research was conducted using the experimental test tools Evaporative Air Cooler Honymell CS12AE. Variables used are temperature cooling medium (water) that is 10, 20, 30, 40, and 500C and the wind speed is (4,57m/s), (3.9 m/s), and (2,93m/s). The data used is the wet bulb temperature and dry bulb temperature on the back of the fan, the temperature of the wet bulb and dry bulb temperature in front of the fan and then the temperature of the wet bulb and dry bulb in the room. Data were taken every 10 minutes for 180 minutes. The test results are temperature cooling medium (water) effect on the relative humidity. The highest humidity is achieved at a temperature of the cooling medium (water) 500C ± 30C and the fan speed ishigh with 92.83% relative humidity. And the lowest humidity was 85.87% at a temperature of 100C ± 30C with a cooling medium high fan speed. Coolant temperature effect on the results of the efficiency and the rate of evaporation of water masses. The highest efficiency on the cooling medium temperature of 100C± 30C with an efficiency of 5.42% with a high fan speed. The highest rate of evaporation of the water mass occur at a temperature of 500C ± 30C cooling medium is 0.00039821 kg/s.Keyword : efficiency, relative humidity, tdb, twb.